Looking within: exploring the effects of social identity-based reflection on novice designers’ task clarification behavior - Evan Brown; Rohan Prabhu (Design Science)
Human-centered design involves designing for users who may have social identities that are dissimilar from designers’ social identities. These differences could impact designers’ ability to understand users’ needs and integrate considerations of social identity into design decisions. Reflective interventions could encourage designers to actively consider social identity in design and our aim in this research is to explore this hypothesis through an experimental study. We tested the effects of completing a social identity-based reflection exercise on novice designers’ task clarification behavior. We also qualitatively examined the quality and content of the reflection responses. We find that participants who completed the intervention generated more social identity-focused design requirements, irrespective of the persona provided to them. Additionally, the content analysis revealed that designers who occupy minority identities (e.g., women and students of color) were more likely to provide deeper and higher-quality reflection responses. These findings suggest that reflective interventions could be an effective mechanism to promote inclusive design, leading to the design of products that users across social identities can use equitably. Furthermore, designers with different social identities may require different reflection cues (e.g., ones more focused on their personal experiences), to encourage deeper reflection on the effects of social identity in design.